Anti‐CD2 producing pig xenografts effect localized depletion of human T cells in a huSCID model. (27th February 2013) - Brady, Jamie L.; Sutherland, Robyn M.; Hancock, Manuela; Kitsoulis, Susie; Lahoud, Mireille H.; Phillips, Peta M.; Hawthorne, Wayne J.; d'Apice, Anthony J. F.; Cowan, Peter J.; Harrison, Leonard C.; O'Connell, Philip J.; Lew, Andrew M.
Abstract Background We investigated whether graft produced anti‐human CD2, mediated by adenovirus (Adv) transduction of pig neonatal islet cell clusters (pNICC), would protect xenografts in a humanized mouse model from immune attack and whether such immunosuppression would remain local. Methods A mouse anti‐human CD2 Ab (CD2hb11) previously generated by us was genetically engineered to produce chimeric and humanized versions. The three forms of CD2hb11 were named dilimomab (mouse), diliximab (chimeric) and dilizumab (humanized). All 3 forms of CD2hb11 Ab were tested for their ability to bind CD3+ human T cells and to inhibit a human anti‐pig xenogeneic mixed lymphocyte reaction (MLR). They were administered systemically in a humanized mouse model in order to test their ability to deplete human CD3+ T cells and whether they induced a cytokine storm. An adenoviral vector expressing diliximab was generated for transduction of pNICC. Humanized mice were transplanted with either control‐transduced pNICC or diliximab‐transduced pNICC and human T cells within grafts and spleens were enumerated by flow cytometry. Results Dilimomab and diliximab inhibited a human anti‐pig xenogeneic response but dilizumab did not. All 3 forms of CD2hb11 Ab bound human T cells in vitro though dilimomab and diliximab exhibited 300‐fold higher avidity than dilizumab. All 3 anti‐CD2 Abs could deplete human CD3+ T cells in vivo in a humanized mouse model without inducing upregulation of activation markers or significant release of cytokines. Humanized mice transplanted with diliximab‐transduced pNICC afforded depletion of CD3+ T cells at the graft site leaving the peripheral immune system intact. Conclusions Local production of a single Ab against T cells can reduce graft infiltration at the xenograft site and may reduce the need for conventional, systemic immunosuppression.